ANALISIS PELAYANAN PEMBUATAN E-KTP DI KABUPATEN KLATEN - Widya Ayu Titaningrum; Tri Murwaningsih; Anton Subarno (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2021)
The type of this study is qualitative research using with a narrative inquiry approach. The sampling techniques used in this study are purposive sampling and snowball sampling. The data collected in this study were obtained from the results of interviews, observations, and documentation. The validity of the data obtained from the process of technical triangulation and source triangulation. The data analyis technique used is an interactive model. The results show a) the implementation of the electronic identification card making service in Klaten Regency is carried out by implementing 2 service systems, namely online services and offline services. Based on the application of (1) the service has a clear legal basis, (2) the service is tailored to the interests and goals, (3) it has social goals, (4) responsiveness, (5) responsibility; b) the factors that affect the service of making electronic identification card in Klaten regency are less optimal, are (1) the service evaluation that is only done based on complaints, (2) network disconnection due to power outage, (3) damaged/collapsed service buildings, and (4) people who still do not know about the online service yet, c) the efforts to solve the problem of making electronic identification card service at the Population and Civil Registration Office of Klaten Regency, are (1) provision of complaint facilities, (2) the use of social media, (3) move building, and (4) socialization to disseminate information about online service.